Peluang Mengembangkan Kewirausahaan Desa Berbasis Potensi Desa - Sukarta Atmaja (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2019)
The government program is currently looking at villages that have the potential to be developed into a tourist center in the hope of changing the lives of rural communities. This research report aims to increase village entrepreneurship opportunities based on village potential. By using descriptive analytical methods, information gathering was obtained from the KKM results of Banten Jaya University students which were divided into 3 subdistricts in Serang Regency and one of them was in Padarincang Subdistrict, Kalumpang Village. The results of the study revealed that the opportunities for village entrepreneurship development were very large and were categorized as small businesses. Its superior products are agriculture, plantations and the potential use of natural resources. The entrepreneurship prospects in the villages have good opportunities provided they are supported by infrastructure, favorable regulations for business actors and the trust of other parties to establish partnerships with entrepreneurs in rural areas.